Implications of hormonal carcinogenesis for transgender and gender-diverse people undergoing gender-affirming hormone therapy: an up-to-date review - Matteo Lambertini; Filippo Pietrantonio; Dario Trapani; Francesco Perrone; Rossana Berardi; Saverio Cinieri; Chiara Cassani; Amelia Barcellini; Filippo Ghelardi; Alberto Giovanni Leone; Stefania Bonadonna; Marianna Sirico; et al. (BMJ Oncology)
Transgender and gender-diverse (TGD) individuals face an elevated risk of cancer in comparison with the general population. This increased risk is primarily attributed to an imbalanced exposure to modifiable risk factors and a limited adherence to cancer screening programmes, stemming from historical social and economic marginalisation. Consequently, these factors contribute to poorer clinical outcomes in terms of cancer diagnosis and mortality. A focal point of interest is the potential carcinogenic effect of gender-affirming hormone therapy (GAHT). It is crucial to recognise that GAHT serves as an essential, life-saving treatment for TGD individuals. Therefore, if a demonstrated direct correlation between GAHT and elevated cancer risk emerges, essential shared decision-making discussions should occur between oncology practitioners and patients. This narrative review aims to collect and discuss evidence regarding potential correlations between GAHT and the most prevalent tumours known to be influenced by sex hormones. The objective is to comprehend how these potential carcinogenic effects impact health and inform health interventions for TGD individuals. Unfortunately, the scarcity of epidemiological data on cancer incidence in the TGD population persists due to the absence of sexual orientation and gender identity data collection in cancer centres. Consequently, in most cases, establishing a positive or negative correlation between GAHT and cancer risk remains speculative. There is an urgent need for concerted efforts from researchers and clinicians worldwide to overcome barriers and enhance cancer prevention and care in this specific population.